DAKWAH STRATEGY IN SOCIAL MEDIA - Sony Eko Adisaputro; Sutamaji sutamaji (Al-Tsiqoh : Jurnal Ekonomi dan Dakwah Islam, 2021)
Da'wah is the obligation of every Muslim that must be carried out continuously, with the ultimate aim of changing human behavior based on correct knowledge and attitudes. Starting from the presence of the Prophet Muhammad SAW who was sent to earth and began his preaching for the first time. Until now, da'wah activities are still being carried out, because da'wah is a mandate for every Muslim in continuing the noble duties of the Prophet Muhammad. Da'wah activities are often interpreted in a narrow sense. Along with the times, in the 21st century there has been a globalization syndrome. The first is marked by the entry of technology which is then followed by the use of the internet and its various applications. Social media (social network) is a continuation of the flow of globalization that entered the virtual world.